LIME AND GYPSUM APPLICATIONS ON SOIL CHEMICAL ATTRIBUTES AND INITIAL GROWTH OF EUCALYPTUS - Gabriel, Camila Adaime; Cassol, Paulo Cezar; Simonete, Marcia Aparecida; Moro, Letícia; Pfleger, Priscylla; Mumbach, Gilmar Luiz (Floresta, 2018)
Eucalyptus crops in Southern Brazil are generally conducted in acidic soils, thus their yield can be increased by lime and gypsum applications. The objective of this study was to evaluate the effect of lime and gypsum applications on soil chemical attributes and initial growth of Eucalyptus benthamii and Eucalyptus dunnii in a Humic Cambisol (Inceptisol). The experiment was conducted in a greenhouse, with seedlings of both species of eucalyptus grown in soil treated with different rates of lime (0, 3, 6, and 12 Mg ha-1), and gypsum (0, 6, 3, 12.6, and 25.2 Mg ha-1). At 90 days after application of the treatments, the soil chemical attributes and growth components of eucalyptus seedlings. The lime increased the production shoot dry weight, however, the response to gypsum was negative. The lime increased the soil pH, exchangeable calcium (Ca), base saturation (V %), and slightly the soil electrical conductivity, decreased the soil aluminium saturation (m %), and promoted little reduction in the exchangeable potassium (K) and magnesium (Mg) contents. The gypsum didn’t alter the soil pH, but decreased the m%, increased soil phosphorus (P) contents, and expressively increased the electrical conductivity, which may have had a negative effect on the eucalyptus growth. In conclusion, the addition of limestone decreases the soil acidity and benefits the growth of eucalyptus seedlings. However, the addition of gypsum has no expressive effects upon those variables, but it can decrease the growth of seedlings when the rates are excessive.